Physical Fitness Assessment Using the TKPN Method for Male Students at SMAN 01 Hulu Gurung Kapuas Hulu Regency - Rio Wardhani; Zainal Arifin (UNIVERSITAS NEGERI MAKASSAR, 2024)
Male students aged 15-16 years at SMAN 01 Hulu Gurung have low physical fitness levels. This is evident from their body mass index status, flexibility, muscle strength, and cardiovascular endurance. This situation can affect the learning process of physical education at school. This study aims to determine the physical fitness of male students at SMAN 01 Hulu Gurung, Kapuas Hulu Regency, within the age range of 15-16 years. The study design used a cross-sectional method, where 91 male students aged 15-16 years were given the TKPN (National Student Fitness Test) method. Data collection involved five test items: (1) body mass index, (2) v sit and reach, (3) sit up, (4) squat thrust, and (5) pacer test. The results showed that 55 students (60.4%) were in the normal category for body mass index, 46 students (51%) were in the low category for the v sit and reach, 40 students (44%) were in the low category for sit up, 33 students (36.2%) were in the low category for squat thrust, and 59 students (64.9%) were in the very low category for the pacer test. Therefore, physical fitness assessments need to be conducted at the beginning of the learning sessions so that the student's physical fitness status can be identified and improved through physical activities at school.